Development of a Culturally Tailored Care Model for Chronic Disease Management in The Coastal Community: A Modified Delphi Study - Laode Saltar; Heltty Heltty; Sitti Mikarna Kaimuddin (Fakultas Ilmu Keperawatan Universitas Indonesia, 2026)
Chronic noncommunicable diseases (NCDs), particularly hypertension and type 2 diabetes mellitus, are increasing in Indonesia’s coastal communities, including the Bajo population of Konawe. Limited healthcare access, cultural barriers, and low preventive health engagement exacerbate disease burden. Culturally tailored interventions are needed to enhance self-awareness and improve chronic disease management. This study aimed to develop and validate a culturally sensitive care model for chronic disease management in the Bajo coastal community using a modified Delphi approach. A three-round modified Delphi method was conducted with 26 panelists representing health professionals, community leaders, policymakers, and family members, recruited through Community Health Centers and community health worker networks. The first round gathered qualitative input on cultural values, traditional practices, barriers, and care model components. The second and third rounds quantitatively assessed proposed components for consensus, defined as ≥75% agreement with ratings ≥4 on a 5-point Likert scale. Eleven of twelve proposed components achieved full consensus. High-priority elements included integration of traditional and biomedical care, family and community involvement, culturally relevant health education, flexible service schedules, and routine free health checks. The panel emphasized communication in local language, engagement of trusted local figures, and culturally competent health workers. One component, the use of local broadcasting media, was rejected because it was perceived as having low feasibility. This study presents a culturally sensitive care framework that operationalizes cultural integration through traditional-biomedical collaboration, family engagement, culturally adapted education, and community-based screening for Indigenous and remote settings. Future studies should prioritize pilot implementation and evaluation of feasibility, acceptability, and health outcomes in coastal settings.